2012
DOI: 10.5194/amt-5-363-2012
|View full text |Cite
|
Sign up to set email alerts
|

A fast and precise chemiluminescence ozone detector for eddy flux and airborne application

Abstract: Abstract.A commercially available dry chemiluminescence (CI) instrument for fast and precise measurement of ozone (O 3 ) is specified. The sensitivity is ∼9000 counts s −1 per ppbv of ozone. Its precision is entirely determined by the number of photons reaching the detector (being a photomultiplier), i.e. is quantum-noise limited. The relative precision . At typical O 3 mixing ratios between 10 and 100 ppbv (and 1 bar), the precision is 0.3-1.0 % at f = 10 Hz. The maximum measurement frequency is 50 Hz. The me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 31 publications
9
95
1
Order By: Relevance
“…19), the model results compare well with measurements (see Zahn et al, 2012, for instrument specifics). The seasonal cycle is reproduced, but the lower values in the troposphere are generally overestimated by up to 40 % by the model.…”
Section: Chemistry In the Upper Troposphere And Lower Stratosphere (Usupporting
confidence: 66%
“…19), the model results compare well with measurements (see Zahn et al, 2012, for instrument specifics). The seasonal cycle is reproduced, but the lower values in the troposphere are generally overestimated by up to 40 % by the model.…”
Section: Chemistry In the Upper Troposphere And Lower Stratosphere (Usupporting
confidence: 66%
“…This response time is based on a number of instrumental operating variables, including the reaction chamber volume and pressure, purge rate, PMT response, and the electronic processing of the signal. Zahn et al (2012) calculated a reaction time as the time required for the ozone signal to drop by 90 % and showed that increasing the sample tubing length increased the response time for a fixed flow rate. In our instrument, the response time without the Nafion dryer installed was 0.31 ± 0.03 s. With the addition of the Nafion dryer, the response time was 0.32 ± 0.03 s. Consequently, under the experimental conditions applied here, the addition of the Nafion dryer did not have a statistically significant effect on the response time.…”
Section: Instrumentation and Methodologymentioning
confidence: 99%
“…An ozone measurement technique with faster response, meeting the requirements for eddy covariance flux observations, is by chemiluminescence, where light emitted from the reaction of ozone with a chemical reactant is used as a measure of ozone concentration. There are several options for the chemiluminescence measurements of ozone, including wet and dry techniques that use organic dyes (Guesten and Heinrich, 1996;Weinheimer, 2006;Zahn et al, 2012), and gas-phase techniques that are based on the reaction of ozone with either ethylene or nitric oxide (Kleindienst et al, 1993;Williams et al, 2006;Bariteau et al, 2010). Current gas-phase chemiluminescence ozone instruments typically use nitric oxide as the reactant gas as it provides a higher signal to noise ratio than from the reaction with ethylene (Ridley et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For each TRAC sample, values for continuously measured trace gases are determined by integration over the sampling period. Ozone (O 3 ) measurements used in this study were measured using a custom-made dual-beam UVphotometer, developed and maintained by the Institute for Meteorology and Climate Research, Karlsruhe, Germany with a time resolution of 4 s and a precision of 0.5 ppb or 0.5 % (whichever is the larger) and a total uncertainty of 1.5 % (Brenninkmeijer et al, 2007;Zahn et al, 2012). Ozone mixing ratios are reported in this study as wet-air mole fractions, nmol mol −1 (air), abbreviated here to ppb (parts per billion).…”
Section: Methodsmentioning
confidence: 99%